Call centry на основі CTI CRM-системи - Радченко, Р. В. (ХНУРЕ, 2022)
The most important mission and task of all organizations, business structures and enterprises is to obtain maximum income. The possibility of instant and effective access to timely information, its analysis, review and distribution give the employee the opportunity to use it appropriately. CTI CRM systems are seamless integration or merging of computers and telephone systems. CTI is also defined as a technology platform that integrates voice and data services at the functional level to add tangible benefits to business applications. To achieve a high level of customer satisfaction, many call centers today use CTI technology in PSTN.